1999
DOI: 10.1074/jbc.274.28.19762
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Ras·GTP Loading and Ras-Raf Association in Neonatal Rat Ventricular Myocytes by G Protein-coupled Receptor Agonists and Phorbol Ester

Abstract: The small G protein Ras has been implicated in hypertrophy of cardiac myocytes. We therefore examined the activation (GTP loading) of Ras by the following hypertrophic agonists: phorbol 12-myristate 13-acetate (PMA), endothelin-1 (ET-1), and phenylephrine (PE). All three increased Ras⅐GTP loading by 10 -15-fold (maximal in 1-2 min), as did bradykinin. Other G protein-coupled receptor agonists (e.g. angiotensin II, carbachol, isoproterenol) were less effective. Activation of Ras by PMA, ET-1, or PE was reduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
60
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 103 publications
(67 citation statements)
references
References 75 publications
5
60
2
Order By: Relevance
“…In particular, microinjection of constitutively active forms of Ras recapitulated the hypertrophic program with an increase in cell size and the enhanced expression of hypertrophic markers such as ANF (4). In addition, stimulation with hypertrophic agents such as phenylephrine leads to an increase in Ras-GTP levels (5). These in vitro studies have been complemented with in vivo experiments that demonstrated increased left ventricular mass and increased ANF expression in cardiac-targeted transgenics expressing a constitutively active ras gene product (6).…”
mentioning
confidence: 63%
“…In particular, microinjection of constitutively active forms of Ras recapitulated the hypertrophic program with an increase in cell size and the enhanced expression of hypertrophic markers such as ANF (4). In addition, stimulation with hypertrophic agents such as phenylephrine leads to an increase in Ras-GTP levels (5). These in vitro studies have been complemented with in vivo experiments that demonstrated increased left ventricular mass and increased ANF expression in cardiac-targeted transgenics expressing a constitutively active ras gene product (6).…”
mentioning
confidence: 63%
“…In addition, PKC, independent of Ras, plays a critical role in angiotensininduced Raf1 and MEK activation in cardiac myocytes (Zou et al, 1996), and PKCd activates the MEK/ERK pathway, independent of Ras but dependent on Raf activation, in COS and NIH-3T3 cells (Ueda et al, 1996;Seternes et al, 1999). In contrast, other studies have shown that PMA/PKC regulates downstream gene induction and functions through sequential induction of Ras, Raf and MEK (Chiloeches et al, 1999;Verin et al, 2000;Vuong et al, 2000); these effects appear to be dependent on cellular context. In our present study, cotransfection with a dominant-negative Raf effectively inhibited TRAF1 promoter induction by PMA.…”
Section: Discussionmentioning
confidence: 91%
“…There has been some controversy in the literature (for example, see Refs. [42][43][44][45][46][47][48][49] regarding the ability of PKC signaling to activate Ras. Our study confirms the ability of PMA to promote PKC-dependent GTP loading of Ras and, to our knowledge, provides the first evidence that Bryo can also produce this effect.…”
Section: Discussionmentioning
confidence: 99%